2014
DOI: 10.1016/j.jpainsymman.2013.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Pain Predicts Subsequent One-Year Acute Health Care Utilization Among Adults With Sickle Cell Disease

Abstract: Context Patient demographic and clinical factors have known associations with acute health care utilization (AHCU) among patients with sickle cell disease (SCD), but it is unknown if pain measured predominantly in an outpatient setting is a predictor of future AHCU in patients with SCD. Objectives To determine whether multidimensional pain scores obtained predominantly in an outpatient setting predicted subsequent one-year AHCU by 137 adults with SCD and whether the pain measured at a second visit also predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 18 publications
0
65
0
Order By: Relevance
“…There was no statistical association between utilization and rs1800587 in additive, dominant or recessive models (incident rate ratio Table 4) [26]. These findings suggested that IL1A rs1800587 influenced baseline, but not acute, pain in SCD.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…There was no statistical association between utilization and rs1800587 in additive, dominant or recessive models (incident rate ratio Table 4) [26]. These findings suggested that IL1A rs1800587 influenced baseline, but not acute, pain in SCD.…”
Section: Resultsmentioning
confidence: 90%
“…Number of utilization ranged from 0 to 38 within 1 year. Three groups are created from utilization rates: 0 utilization (15% of total patients), 1-3 (45%) and 4-38 (40%) based on previous studies where the distribution of acute healthcare utilization events were taken into account 4 [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects completed a multidimensional computerized pain assessment using PAINReportIt ®2,16 to record baseline pain location, intensity, quality, and pattern during a routine outpatient clinic visit. PAINReportIt® is an electronic touch screen format of the 1970 version of MPQ (McGill Pain Questionnaire) 17 that can be self-administered by the patient with little or no computer experience.…”
Section: Methodsmentioning
confidence: 99%